Computer literacy, attitude to computer and learning styles as predictors of physics students' achievement in senior secondary schools of Oyo State (2019)
Physics, a subject in the senior secondary school occupies a central position in science education. Physics in this 21st century as a course of study and field is experiencing new discoveries at such a rate that it cannot continue to be taught using only traditional and conventional method and the teacher-centred approach. The invention of computer-based resources for teaching the subject would be a great advantage if explored. Hence, the factors which impede students’ use of computer technology in learning of Physics however need to be investigated. This study investigated three of these factors and found that student’s computer literacy, attitude to computer and learning styles jointly correlate with achievement of students in Physics (R = 0.18) with each factor making respective relative contributions. While computer literacy could not predict the dependent measure (B= -0.055; t = -0.67; p<0.05), attitude to computer could (B- 0.18; t = -1.09; p>0.05) and learning styles could not (B= 0.20; t = 0.25; p>0.05). It was recommended that Physics students should be motivated to learn and be equipped with computer appreciation and operational skills while computer systems need to be made available and accessible for Physics learning in the school system.